Pengaruh Transportasi Umum Terhadap Perkembangan Antar Wilayah Administrasi di Jakarta - Putri, Nasha Indi Pratama (Institut Transportasi dan Logistik Trisakti, 2022)
Public transportation plays an important role in the economic growth of a city by increasing people's mobility, distributing goods and services, and encouraging investment. One of the cities with the best public transportation in Indonesia is Jakarta. This study aims to analyze the effect of public transportation on people's mobility and the economy between administrative areas in Jakarta. The research method uses descriptive qualitative analysis using secondary data from the Central Statistics Agency (BPS) and Ministry Relationship Directorate General Railways. The research focuses on the transportation and warehousing sector by using GDP as an indicator of economic growth. Research results show high mobility in Jakarta has an impact on economic and sector growth transportation contribute to GRDP. Public transportation such as Transjakarta and Commuter Line Trains are the main choices in transportation mobility for Jakarta residents who reflect awareness of continuity, reduce traffic congestion and contribute to the development economy besides That Transportation common in Jakarta facilitates delivery of goods and services. Efficient transportation development and integration carried out by the Jakarta government is key in supporting economic growth and mobility of people, goods and services in Jakarta.